Análisis y Diseño de un Sistema de Antena Adaptativa con Algoritmos Genéticos - Flórez, Mauro; Ospina, Martha Ruth; Galindo Cepeda, William Francisco (Ingeniería, 2004)
This paper studies concepts about linear antenna arrays, designed with genetic algorithms. Each antenna fed with combined amplitude and phase control to adjust side lobe levels and steer nulls. Also, the number of elements and the spacing between them are adjusted.